Development of Multiple Bio-Signals Microcontroller-based Wearable Device for Human Stress Monitoring Application - Jumaat Ali, Aminatul Saadiah; Abdullah, Latifah; Tukiran, Zarina; Ismail, Nurulhuda (Evolution in Electrical and Electronic Engineering, 2021)
Stress is inevitable, however, overstress needs to be managed before affects a person’s health. One way to monitor a person’s stress is by evaluating the body bio-signals and heart rate is the most common approach. In the market, various wearable devices measured only heart rate – which might contribute to a false alarm. This work is an attempt to develop a wearable device that can measure stress based on two bio-signals; heart rate and skin conductance. In this work, the photoplethysmography (PPG) sensor and Galvanic Skin Response (GSR) sensor are used to measure the heart rate and skin conductance, respectively. Then, the ATmega328P microcontroller process the data and display the output of “Not Stressed” or “Stressed” on the LCD. There are two experiments; (i) analyse the accuracy of sensor measurement and (ii) evaluate the overall performance of the prototype. The first experiment concludes there is an insignificant different measurement for the PPG sensor when compared to the commercial heart rate application. For the second experiment, the findings from four adult healthy subjects conclude the device able to produce the correct output as expected.